Measurement of the 13C isotopic signature of methane emissions from northern European wetlands. Issue 3 (31st March 2017) - Fisher, Rebecca E.; France, James L.; Lowry, David; Lanoisellé, Mathias; Brownlow, Rebecca; Pyle, John A.; Cain, Michelle; Warwick, Nicola; Skiba, Ute M.; Drewer, Julia; Dinsmore, Kerry J.; Leeson, Sarah R.; et al.
Abstract: Isotopic data provide powerful constraints on regional and global methane emissions and their source profiles. However, inverse modeling of spatially resolved methane flux is currently constrained by a lack of information on the variability of source isotopic signatures. In this study, isotopic signatures of emissions in the Fennoscandian Arctic have been determined in chambers over wetland, in the air 0.3 to 3 m above the wetland surface and by aircraft sampling from 100 m above wetlands up to the stratosphere. Overall, the methane flux to atmosphere has a coherent δ 13 C isotopic signature of −71 ± 1‰, measured in situ on the ground in wetlands. This is in close agreement with δ 13 C isotopic signatures of local and regional methane increments measured by aircraft campaigns flying through air masses containing elevated methane mole fractions. In contrast, results from wetlands in Canadian boreal forest farther south gave isotopic signatures of −67 ± 1‰. Wetland emissions dominate the local methane source measured over the European Arctic in summer. Chamber measurements demonstrate a highly variable methane flux and isotopic signature, but the results from air sampling within wetland areas show that emissions mix rapidly immediately above the wetland surface and methane emissions reaching the wider atmosphere do indeed have strongly coherent C isotope signatures. The study suggests that for boreal wetlands (>60°N) global and regional modeling can use an isotopic signature of −71‰ to apportion sources more accurately, but there is much need for further measurements over other wetlands regions to verify this. Key Points: Methane δ 13 C isotopic signatures of northern European wetland emissions have been measured in air samples collected at different scales Wetland emissions dominate the methane source measured over northern Fennoscandia in summer aircraft campaigns The δ 13 C isotopic signature of emissions from northern European wetland to atmosphere is well constrained